PELATIHAN PENGELOLAAN KEUANGAN DESA MENGGUNAKAN APLIKASI SISTEM KEUANGAN DESA (SISKEUDES) DI DESA MENDALO INDAH KECAMATAN JALUKO KABUPATEN MUARO JAMBI - Rita Friyani; Enggar Diah Puspa Arum; Netty Herawaty; Yuliana Yuliana; Riski Hernando (JURNAL DAYA-MAS, 2022)
Devotion to Society is titled: "Village Financial Management Training using Village Financial System Application in Mendalo Indah Village of Jaluko District muaro Jambi". Given the limited knowledge and skills possessed by village heads, village devices, and members of village consultative bodies in managing village finances as an implementation of Law No. 6 of 2014 on Villages and Government Regulation No. 43 of 2014 on Village Law Implementation Regulations that began to be implemented through the State Budget in 2015, it is considered necessary to perform community service through Training to village heads,Â  and village devices. Through this village financial management training is expected to help the village head, and village devices, can manage village finances properly and correctly based on applicable laws and regulations starting from the preparation of program plans, the preparation of village medium-term development plans (RPMJDesa), preparation of village program activity plan (RKPDesa), preparation of a detailed list of village activities (DRKDesa) and preparation of village revenue and expenditure budget (APBDesa), as well as recording of recipients and expenditures, implementation of APBDesa, accountability report, evaluation and monitoring and completeness and validity of documents.